Mechanics and mechanisms of fatigue in a WC–Ni hardmetal and a comparative study with respect to WC–Co hardmetals. (January 2015) - Tarragó, J.M.; Ferrari, C.; Reig, B.; Coureaux, D.; Schneider, L.; Llanes, L.
Highlights: Flexural strength and fracture toughness of a WC–Ni hardmetal are determined. Fatigue behavior of a WC–Ni hardmetal is assessed. FCG threshold is validated as the effective fracture toughness under cyclic loading. Fatigue sensitivity of Ni- and Co-based hardmetals is found to be similar. FCG features are related to comparable binder–cyclic plastic zone length scales. Abstract: There is a major interest in replacing cobalt binder in hardmetals (cemented carbides) aiming for materials with similar or even improved properties at a lower price. Nickel is one of the materials most commonly used as a binder alternative to cobalt in these metal-ceramic composites. However, knowledge on mechanical properties and particularly on fatigue behavior of Ni-base cemented carbides is relatively scarce. In this study, the fatigue mechanics and mechanisms of a fine grained WC–Ni grade is assessed. In doing so, fatigue crack growth (FCG) behavior and fatigue limit are determined, and the attained results are compared to corresponding fracture toughness and flexural strength. An analysis of the results within a fatigue mechanics framework permits to validate FCG threshold as the effective fracture toughness under cyclic loading. Experimentally determined data are then used to analyze the fatigue susceptibility of the studied material. It is found that the fatigue sensitivity of the WC–Ni hardmetal investigated is close to that previously reported for Co-base cemented carbides with alike binder mean free path. Additionally, fracture modes under stable and unstable crack growth conditions are inspected. It is evidenced that stable crack growth under cyclic loading within the nickel binder exhibit faceted, crystallographic features. This microscopic failure mode is rationalized on the basis of the comparable sizes of the cyclic plastic zone ahead of the crack tip and the characteristic microstructure length scale where fatigue degradation phenomena take place in hardmetals, i.e. the binder mean free path.